2022
DOI: 10.1055/s-0042-1751082
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Food Security and Gestational Diabetes among Pregnant Women

Abstract: The objective were to: (1) evaluate associations between food security and women diagnosed with gestational diabetes mellitus (GDM) and (2) evaluate if women in food insecure (FI) households had adverse maternal and neonatal outcomes. This was an observational study from October 2018 until September 2019. Postpartum resident clinic patients who delivered term, singleton infant at 37 weeks' or longer gestation were screened. Participants completed a survey using the U.S. Household Food Security Survey Module (U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…However, the healthcare providers felt depression was not associated with GDM, studies in the past have demonstrated association between physical activity and GDM [20,21] as well as diet intake and GDM [20][21][22]. Similarly, other studies in the past have also reported on association between food security and GDM [23,24]. This study is not without limitation, for instance only ve participants were interviewed, which could raise concerns about generalisability of our ndings.…”
Section: Discussionmentioning
confidence: 69%
“…However, the healthcare providers felt depression was not associated with GDM, studies in the past have demonstrated association between physical activity and GDM [20,21] as well as diet intake and GDM [20][21][22]. Similarly, other studies in the past have also reported on association between food security and GDM [23,24]. This study is not without limitation, for instance only ve participants were interviewed, which could raise concerns about generalisability of our ndings.…”
Section: Discussionmentioning
confidence: 69%
“…Seven studies 44,45,47,50,54,58,59 reported data on associations between food insecurity and women having an obese BMI and could be pooled in a meta-analysis (Table S7). The pooled data showed a significant association between food insecurity and pre-pregnancy obesity (OR 1.53, 95%CI 1.39, 1.66, I 2 0%) (Figure 2).…”
Section: Food Insecurity and Pre-pregnancy Bmimentioning
confidence: 99%
“…One study 45 also reported a significantly increased median BMI in food insecure women compared with food secure, and one reported a significantly increasing BMI with food insecurity score. 58…”
Section: Food Insecurity and Pre-pregnancy Bmimentioning
confidence: 99%
“…Additionally, the mother's body transfers folate to the developing fetus [14], raising the need for folate beyond just her own needs. [16][17][18][19] Among the women at risk for poor folate status • Those who do not take the necessary dosage of folic acid supplements;…”
Section: B Folic Acid and Pregnancymentioning
confidence: 99%